Unggul Daycare Human Resource Business Planning - Mohammad Munir; Tantri Yanuar Rahmat Syah; Samerdanta Pusaka; Rokiah Kusumapradja (Penerbit Kemala Indonesia, 2019)
The objective in this business planning Unggul Daycare is a child care agency for children in 3 to 6 years it means that the temporally subside a parenting role in caring and nursing children by providing the best service to meet customer demand for customer satisfaction. The basic analysis and operational thinking of daycare is performed using HR stages or HR model consisting of strategy, system, staffing, share value, structure, skill and style. Strategic location is needed to support daycare business, the observation location at Head Office PT. ASABRI (Persero), Jalan Mayjen Sutoyo No. 11, Cawang, East Jakarta.